ANALYSIS OF CODE SWITCHING AND CODE MIXING ON THE ALBUM GREETINGS BY HARIS J - Maula, Jechan Shofwatul (Jurnal Penelitian Humaniora, 2023)
ABSTRACT The phenomenon of using code switching and code mixing has become a thing in multilingual communities which is common when daily communication activities take place. Apart from that, there is the phenomenon of code switching and code mixing is not only found in everyday communication activities, but this phenomenon also occurs in song lyrics, especially in the current digital music era This. Likewise, the songs on the album Salam by Haris J experienced a transfer phenomenon code and code mixing. This research describes the forms and factors of code switching and code mixing in the songs on the Salam album by Haris J. This research method using descriptive methods with a qualitative approach. Data collection technique in this research, the SBLC technique (simak bebas, libat cakap) and the Katat technique were used. Song lyric data containing code switching and code mixing is explained based on theory Poedjosoedarmo (1976) and Suwito (1983). Factors causing code switching and code mixing the explanation is based on Fishman's theory (in Chaer Leane, 2010) and Hoffman Troike (in Trilipita, 2016). The results of data analysis show a form of code switching in song lyrics the Salam album is temporary code switching, while the forms of code mixing are: 1) words, 2) clause, 3) phrase, 4) reword. The code-switching factors found were speaker, listener, and situation change. Code mixing factors foun namely: 1) Talking about a topic, 2) Efficiency conversation, 3) lexical needs, 4) fillers and sentence connectors